PAPARAN ASAP ROKOK SEBAGAI FAKTOR RISIKO ASMA PADA ANAK DENGAN RINITIS ALERGIKA - , Rillya Emilda, dr. Sumadiono, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Forty percent of the children had rhinitis until reaching the age of 6 years. Allergic rhinitis is often associated with a number of comorbid conditions, including bronchial asthma. Cigarette smoke exposure in children causes more severe effects than adults due to the narrow diameter of the respiratory tract children, so the cigarette smoke coming into the airways become more than his weight. Objective: To find out how did smoke exposure become a risk factor for asthma incidence in children allergic rhinitis. Methods: A cross-sectional study was conducted in children with allergic rhinitis. Subjects population of elementary school students in Yogyakarta from December 2010 until Januari 2011. Consecutive sampling was used to select the subjects of the study. by interview using questionnaire